THE SIGNIFICANCE AND ROLE OF USING INNOVATIVE TECHNOLOGIES IN MODERN AGRICULTURAL PRODUCTION - Mladen Petrović; Irina Marina; Marko Jeločnik (Journal of Research and Innovation for Sustainable Society)
In order to succeed to feed the global population in upcoming period, additionally pressed by climate change, or economic shocks and environmental issues, agriculture is forced to be based on innovation and improved technologies. Furthermore, although it mainly works with living organisms and complex chemical processes, it rapidly becomes a part of a digital world. So, current agrifood production ensures food safety and security by the wider use of various drones, robots, sensors, software packages, IoT, etc., enabling business optimization, sustainability and profitability. On other side, in some segments, operating with advanced mechanization, equipment and technology requires specific skills and knowledges form farmers, exposing the user-friendly approach as certain challenge for contemporary science and practice.